REPRESENTATION OF IDENTITY AND THE TITLE OF DIPONEGORO IN INDONESIAN FICTION - Mukti, Wijang Iswara (Prosiding Konferensi Internasional Kesusasteraan, 2025)
Prince Diponegoro was a phenomenal figure who inspired the Javanese people to defend their dignity. His turbulent and dynamic life story has also been a source of inspiration for writers in creating their works. His identity and title in history are widely known, but his identity and title in fiction still need to be explored. This study aims to reveal and describe the representation of Prince Diponegoro's identity and title in Indonesian novels. The approach used in this study is New Historicism. The data sources for this research are four novels set against the backdrop of Prince Diponegoro, namely: 1) Novel Diponegoro: Menggagas Ratu Adil (Diponegoro: Conceiving the Just Queen), 2) Novel Diponegoro: Menuju Sosok Khilafah (Diponegoro: Towards the Figure of the Caliphate), both by Remi Sylado; 3) Sang Pangeran & Janissary Terakhir (The Prince & The Last Janissary) by Salim A. Fillah; and the novel Diponegoro: Pangeran Bermata Tajam Berkilat Iman (Diponegoro: The Prince with Sharp Eyes and Shining Faith) by Yudhi AW. The data collection technique used was reading and note-taking. The data consisted of factual stories, including storylines, characters, settings, themes, and other literary devices from data sources containing information related to the research problem, which were analyzed qualitatively using a new historicism approach. The results of this study show the representation of Diponegoro's identity in Indonesian novels, namely: 1) Javanese aristocrat, 2) born with special qualities, 3) educated outside the palace, 4) close to Islam and Islamic scholars, 5) leader of the Holy War; 6) serving as Wali Sultan, 7) religious and political leader, 8) loved by the people and the commoners; 9) labeled a rebel and became the Dutch's most wanted fugitive. The representation of Diponegoro's titles in Indonesian novels are: 1) Sultan Abdul Hamid, 2) Herucokro, 3) Kabirul Mukminin, 4) Sayyidin Panatagama, 5) Senopati Sabilillah, 6) Khalifah Rasulullah ing Tanah Jawi. Overall, it is understood that Prince Diponegoro was a sultan, a just ruler, a religious leader and administrator, a military commander, and the representative of the Prophet Muhammad in Java for his followers.